(untitled) (Journal of Parents and Teachers, 1995)
Play as a form of expression and learning, where each individual should be authentic and not try to be like someone else. The commercialization of toys is criticized, suggesting that they should encourage creativity and personal discovery. Play is presented as a vital process that allows children and adults to explore their abilities and emotions without frustration.